1994
DOI: 10.1034/j.1600-0501.1994.050306.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate transmucosal implants using the principle of guided tissue regeneration. I. Rationale, clinical procedures and 30‐month results.

Abstract: The installation of implants directly into extraction sockets offers considerable advantages over other treatment modalities for both practitioners and patients. Usually, immediate implants are placed and subsequently covered by mucosa allowing a submerged healing mode. This report presents the rationale, clinical procedures and results for immediate transmucosal implants. Following an intracrevicular incision and flap elevation, the tooth to be extracted is carefully luxated by means of small elevators to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
9

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(91 citation statements)
references
References 0 publications
4
78
0
9
Order By: Relevance
“…The success based on clinical criteria 45,46 has been experimentally documented by Akimoto et al, 47 who showed that small peri-implant defects up to 1 to 1.5 mm can be treated successfully with particulate autogenous bone alone, whereas in larger defects, the addition of a membrane may be needed.…”
Section: Discussionmentioning
confidence: 96%
“…The success based on clinical criteria 45,46 has been experimentally documented by Akimoto et al, 47 who showed that small peri-implant defects up to 1 to 1.5 mm can be treated successfully with particulate autogenous bone alone, whereas in larger defects, the addition of a membrane may be needed.…”
Section: Discussionmentioning
confidence: 96%
“…50,72,73 A consensus has yet to be formed regarding the need for the use of barrier materials and/or bone grafts around immediately placed implants. [74][75][76][77][78] It may be that assuming the critical jumping distance has not been exceeded, the space formed between the extraction socket and implant fixture provides an ideal environment for clot stabilization and subsequent osteogenesis. 79,80 Various animal studies have proved that by excluding the epithelium and connective tissue, a secluded space is thereby created, allowing slowly migrating osteoblast cells to populate the wound, resulting in enhanced bone formation.…”
Section: Space Creation/maintenancementioning
confidence: 99%
“…3,11 In clinical practice, 2 treatment protocols have been used for postextraction implant placement: the submerged protocol [12][13][14] and the nonsubmerged protocol. 15,16 However, these protocols have been progressively challenged to decrease treatment time, minimize the number of surgical procedures, and maximize esthetic outcomes. NowaPurpose: Immediate loading of dental implants inserted into fresh postextraction sites has recently been proposed as a novel but challenging surgical approach.…”
mentioning
confidence: 99%